Relationship of Knowledge, Attitudes, and Preventive Actions to The Incidence of HIV-AIDS in the Men Who Have Sex with Men (MSM) in the Oebobo District Kupang City - Refandro Purumbawa; Petrus Romeo; Helga J. N. Ndun (Lontar : Journal of Community Health, 2022)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS), a sexually transmitted disease, is one of the world's most serious health problems including in East Nusa Tenggara, Indonesia. HIV-AIDS disease can be prevented by being faithful to a sex partner and using condoms during sexual intercourse. "Men who have sex with men" or MSM community is one of the populations at risk of contributing to HIV-AIDS disease due to having anal sex and low preventive behavior. This research aims to find out the relationship between knowledge, attitudes, and preventive measures to the incidence of HIV-AIDS in the MSM community in Oebobo. This research was quantitative with a cross-sectional study design. The population in this research was 410 people in the MSM community located in Oebobo. The sample was determined using a proportional sampling technique with 78 people as a sample number. The data were analyzed using univariate and bivariate with a chi-square test. The results showed that 60.87% of respondents had less knowledge, 75% with negative attitudes, and 78.27% of respondents did not take precautions against the incidence of HIV-AIDS. The incidence of HIV-AIDS can be decreased with better knowledge (95% CI =63.90 to 71.60; p=0.042), positive attitudes (95% CI =75.86 to 80.70; p=0.005), and preventive actions (95% CI =59.62 to 73.70; p=0.002). Health promotion must be carried out continuously and precautions are needed to reduce the risk of HIV-AIDS transmission.